Education Budget Reorientation 2026: A Qualitative Study on the Impact of the Free Nutritious Meal Program on Improving Education Quality - Budi Susanto; Tarwin Tarwin; Sutrisno Sutrisno (FKIP - Universitas Riau, 2026)
The reorientation of the 2026 education budget has generated significant debate due to the large allocation for the Free Nutritious Meal Program, raising concerns about its impact on overall education quality. This study aims to analyze the structure and dynamics of the 2026 education budget allocation and examine its implications for improving education quality. A qualitative research approach was employed using document analysis and policy review of official budget reports and relevant regulations. The findings reveal that the program contributes positively to students’ health, learning readiness, and classroom participation. However, the substantial allocation reduces funding for key sectors such as teacher professional development, educational infrastructure, and learning innovation, indicating a structural imbalance in policy priorities. In conclusion, while the program provides important short-term benefits, a more balanced and strategic allocation is required to ensure that welfare-oriented policies support, rather than hinder, sustainable improvements in education quality.